A-26 The Prevalence of Invalid Baseline ImPACT® Test Scores in Adolescent Student Athletes. (13th July 2022) - Liu, B C; Gaudet, C E; Schatz, P; Berkner, P; Iverson, G L
Abstract: Purpose: Immediate Post-Concussion and Cognitive Testing (ImPACT®) is among the most commonly used neuropsychological measures to establish a baseline estimate of neuropsychological functioning for concussion management. We sought to identify correlates of invalid performance on ImPACT® baseline testing in adolescents. Methods: The sample included 67, 009 English-speaking adolescents (ages 14–18, mean: 15.51, SD: 1.22) who completed ImPACT® baseline tests in English between 2009 and 2019. The association between invalid performance (as determined by the embedded invalidity indicators) and demographic and health variables was assessed using chi-square tests and with odds ratios (OR). Results: Overall, 7.2% of adolescents produced invalid baseline tests. Boys (7.9%) produced more invalid baselines than girls (6.2%; χ 2 = 70.35, p < 0.001, OR = 1.29, 95% CI = 1.22, 1.37). Adolescents with learning disabilities (16.4%), attention-deficit/hyperactivity disorder (11.1%), and those who have received special education services (16.0%) or repeated more than 1 year of school (11.0%), all obtained invalid baselines at higher frequencies than those who did not endorse these variables (i.e., 6.5%–6.8%; p < 0.001). Adolescents who reported receiving treatment for headaches (9.5%), migraines (9.4%), epilepsy/seizures (11.1%), substance/alcohol use (17.0%), or a psychiatric condition (10.0%) obtained invalid baselines at higher frequencies than those who did not (i.e., 6.6%–6.9%; p < 0.001). Conclusions: Consistent with prior research, approximately 7% of adolescents produced invalid baselines. However, the frequencies of invalid performances were substantially greater for subgroups such as those with learning disabilities, those who have received special education services, and youth who have received past substance abuse treatment.